Religiusitas penyandang tunanetra - Mauladi, Muhammad; Reza, Iredho Fani; Kailani, Kailani (Asosiasi Psikologi Islam (API) Himpsi, 2018)
People with blindness is a condition where individual experienced a weak visual impairment or invisible vision. Individuals with visual impairments tend to experience some holistic problems. This research is a type of narrative qualitative study. The subjects of this study were four people with visual impairments. The methods of data collection were used interview, observation, and documentation. The data were analyzed using Miles and Huberman techniques consists of data reduction, data display, and conclusion drawing / verification. The results indicated that religiosity in individuals with visual impairments revealed through a series of worship. This can make an acceptance with full of sincerity toward the life situations. This study also found two dimensions of religiosity in individuals with visual impairments through Islamic psychology perspective. First, hablum min Allah dimension who has behavioral indicators believing in the religion, prayers, zakat, fasting, know the pillars of Islam, harmonizes faith and has a better appreciation to Allah. Second, hablum min an-nas dimension who has prosocial behavior indicators, respect for older people, and advise one another in the kindness. Keywords: Religiosity, Sincerity, Blind People.